The Lone Culinary Codex: A preliminary analysis of the cookbook in MS 23 D 43 and its compatibility with medieval Icelandic foodways - Estefanía Arévalo d'Escriván 1996- (2025)
The focus of this research was the only surviving cookbook in the medieval Icelandic manuscript corpus, the Libellus de arte coquinaria. Both the cookbook and the manuscript that contains it, the RIA MS 23 D 43, have not been widely studied, so the aim of the research was to bring them into the medieval Icelandic context and assess their impact. We sought to understand, through the lens of food history, the compatibility of the recipes in the cookbook with medieval Iceland as well as the role of continental European influence in this. The research consisted in conducting a quantitative and qualitative analyses of the recipes, together with a comparative analysis between those results and medieval Icelandic foodways. This exercise allowed to conclude that while it would have required great effort and wealth to recreate the recipes, and the concession of using substitutions, the recipes did resonate with food practices in Iceland at the time. These results show that not only was medieval Iceland connected and able to receive knowledge from continental Europe, but also that they were actively participating in the circulation of culture and following trends surging in the continent. Additionally, it has provided fruitful insight into medieval Icelandic food history, and hopefully encouraged further research in this area.